Rowan and the Ice-Creepers - Rodda, Emily (New York : Greenwillow Books, 2003)
When a bitter winter threatens starvation to the people of Rin who set out for the coast, Rowan and several others stay behind for various reasons and are led to a startling discovery about their people's past.
Accelerated Reader AR
Keywords: Heroes -- Juvenile fiction; Heroes -- Fiction; Fantasy